Fundamental study on protein expression of several selected harmful algal bloom (HAB) species during different growth phases - Muhamad Bunnori, Noraslinda; Mohammad Noor, Normawaty; Abd Hamid, Shafida (2018)
The naturally occurring phenomenon of harmful algae blooming (HAB) at the water column brought detrimental effects to the economy as well as the environmental health of the water ecosystem. Most cases of HABs reported in Malaysia waters are dominated by dinoflagellates Alexandrium spp. with some of the species were reported to cause shellfish poisoning. In this study, two Alexandrium spp.; A. tamiyavanichii and A. leei with different toxicity levels were analyzed using proteomic approaches involving two-dimensional PAGE and HPLC analysis. The growth pattern of both species were identified and compared through protein profiles for each growth phases that acquired. Protein expression reduced throughout the growth phases of A. tamiyavanichii but elevated during stationary phase of A. leei. A short duration of stationary phase suggests the continuous expression of growth proteins in A. leei. GNAT family acetyltransferase and lipases were successfully identified enzyme protein in A. tamiyavanichii and A. leei respectively with growth regulatory functions. The toxin profiles of both species exhibited higher level of toxin content in A. tamiyavanichii with 88 mol % of total toxins recorded as compared to 12 mol% in A. leei. The highest toxin content was recorded during exponential phase of A. tamiyavanichii with dominance of GTX4 and STX congeners. Further investigation on the toxicity effects of Alexandrium spp. was studied by using oysters where the shellfish are fed with toxic A. tamiyavanichii and non-toxic A. leei. LC-MS results of the two up-regulated spots in oysters fed with A. tamiyavanichii were identified as arginine kinase and transgelin. The up-regulation of the protein was induced as responsive mechanism towards accumulation of the toxic species A. tamiyavanichii. These responses reflect the oyster stability during HAB outbreak. Fundamental studies of dinoflagellates from its molecular as well as byproduct analysis are useful to understand the biochemistry of the HAB species. The findings from this study can provide the basis knowledge on the biochemical properties of HAB species and the behavioral of affected organisms